The Impact of Covid-19 on the Global Stock Market and the Global Retail Industry - AN, KUN (2022)
The Covid-19 outbreak had a profound impact on the development of global integration. Therefore, it becomes particularly critical to explore the impact of the pandemic on the global economy and some specific industries, such as retailing. This study investigates the relationship between stock indexes and some macroeconomic indicators in 25 countries using Vector Autoregression (VAR) models. According to the Granger Causality Test, the stock indexes and macroeconomic indicators were closely connected in most countries. The price of crude oil and the stock index is the most correlated, showing a negative correlation. Meanwhile, the VAR model shows that the development of pandemics suppresses the stock market index of most countries through the increase of Covid-19 and the mortality rate. In addition, this study analyzes the stock prices of nearly 2,000 public retailing companies in the short term and one-year post-pandemic time through the Event Study Methodology (ESM) approach. We find that in the short term, the pandemic severely hits the retail industry in most countries and then gradually decays to a lower level over time. At the same time, the impact of the pandemic is lagged and long-term for the retail sector in other countries. Moreover, the pandemic has the most significant adverse effects on apparel-related retailing and the most negligible impact on food-related retailing. This is primarily due to the lockdown policy and shifting consumer demand. In addition, online-related retailers witnessed significant market share growth during the pandemic. Although offline retailers were severely shocked by the pandemic, their recovery gained remarkable momentum as the lockdown policy was terminated and the government managed the outbreak.